Is there an alternative to diclofenac i/m injections for rapid relief of severe pain? Results of randomized controlled and partially blind forsage study - A. E. Karateev; E. Yu. Pogozheva; E. S. Filatova; A. M. Lila; V. N. Amirdjanova; V. A. Nesterenko (Научно-практическая ревматология)
Diclofenac Potassium sachets (DPS) is a new faster-absorption and rapid onset of pain relief drug dosage form of Diclofenac with high analgesic potential.Objective. To assess efficacy and safety of Diclofenac sachets and intramuscular injections in relieving acute pain in patients with rheumatic diseases (RDs).Materials and methods: The study group included 30 RD patients, 53.3% females and 46.7% males, mean age 41.8 ± 10.7 years, with severe acute pain (≥7 cm VAS pain rating, VAS 0-10 cm). After signing informed consent patients were randomized into DPS 50 mg t.i.d. and Diclofenac 75 mg i/m b.i.d. The first administration of Diclofenac was blind, i.e., patients from both groups were also administered placebo – either placebo injection in Group 1 randomized to sachet or placebo sachet in Group 2. The study lasted for 3 days. Level of analgesia was assessed in 15, 30, 60, 120, 180 minutes after the first administration, then three times a day during two following days and in the morning on day 4. Serum levels of CRP, IL-6 and P substance biomarkers were also monitored.Results. Pain relief in Group 1 was documented already in 15 min after administration – from 8.1±0.8 to 5.7±1.7 cm VAS (р=0.012), with continuing increase of analgesic effect thereafter. Group 2 demonstrated significant pain relief in 1 hour after Diclofenac administration – from 7.6±0.7 to 4.5±1.9 cm VAS (р=0.04). Based on obtained data analgesic effect was more powerful in Group 1 vs Group 2 in 15 and 30 minutes after drug administration (р=0.019; р=0.037). Starting from the 3rd hour post-administration there was no statistically significant difference in pain intensity between the two groups. Final assessment in the morning on day 4 showed significant pain reduction by 4.5±2.6 cm VAS in Group 1 vs baseline, and by 3.6±1.4 cm VAS in Group 2 (p=0.545). Functional improvement in both groups reached 3.7±1.9 and 3.3±1.3 cm VAS, respectively (p=0.837). The results were rated as “good” and “excellent” by 77.0% in Group 1, and 61.5% – in Group 2 (р=0.302). No correlation between decreasing pain intensity and fluctuating CRP, IL-6, and substance P concentrations was established. Three patients from Group 1 reported new-onset dyspepsia, resulting in discontinuation of treatment in 2 of them. Similarly, 2 discontinuations occurred in 2 patients with new-onset dyspepsia in Group 2, plus one additional withdrawal due to gastric ulcer and elevated blood pressure.Conclusion. DPS is not inferior to i/m Diclofenac injections in terms of analgesic potential and rapid onset of pain relief. Oral intake is associated with fewer adverse reactions compared to i/m injections.